Cognitive processing and growth following trauma - Stockton, Hannah (2012)
The possibility of positive psychological change following traumatic life experiences has now been well documented in the literature. This phenomenon is most commonly referred to as posttraumatic growth. Several theoretical models have sought to explain the development of posttraumatic growth, many of which have emphasised the important role of cognitive processing (Calhoun, Cann & Tedeschi, 2010; Tedeschi & Calhoun, 2004a). This thesis sought to further our understanding of the nature of posttraumatic cognitive processing and its association with psychological growth following trauma and adversity. A narrative review of the existing literature on cognitive processing and posttraumatic growth was conducted (Chapter 2) and suggested that cognitive processing might be best understood as comprising intrusive, deliberate and ruminative subtypes. Two cross-sectional studies and one longitudinal study were then conducted to develop and test this conceptualisation using samples of survivors of sexually traumatic experiences (Study 1; n = 123), trauma-exposed individuals recruited from trauma-focused websites and support forums (Study 2; n = 254), and trauma-exposed students from the University of Nottingham (Study 3; n = 174). The influence of these three subtypes of cognitive processing on levels of growth following adversity were also tested using the expressive writing intervention (Study 4; n = 24). Taken together, findings from the four studies supported the conceptualisation of cognitive processing as multidimensional, comprising intrusive, deliberate and ruminative subtypes that are differentially associated with posttraumatic growth. Results also provided consistent evidence to suggest that deliberate processing is especially important in the occurrence of growth following trauma and adversity. Unexpectedly, intrusive processing was not found to positively influence posttraumatic growth in the ways hypothesised by existing theoretical models. Implications of these findings with respect to both further research and clinical work with trauma survivors were reviewed in the final chapter.